2014
DOI: 10.1534/g3.114.013946
|View full text |Cite
|
Sign up to set email alerts
|

The Alternative Oxidase AOX Does Not Rescue the Phenotype oftko25tMutant Flies

Abstract: A point mutation [technical knockout25t (tko25t)] in the Drosophila gene coding for mitoribosomal protein S12 generates a phenotype of developmental delay and bang sensitivity. tko25t has been intensively studied as an animal model for human mitochondrial diseases associated with deficiency of mitochondrial protein synthesis and consequent multiple respiratory chain defects. Transgenic expression in Drosophila of the alternative oxidase (AOX) derived from Ciona intestinalis has previously been shown to mitigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 37 publications
(51 reference statements)
3
20
0
Order By: Relevance
“…Yeast Ndi1 expression was shown previously to complement the lethality (at 25°C) of knockdown of subunits of cI [9] in Drosophila, whilst leaving a residual phenotype [32]. We therefore tested whether NDX was able to act similarly.…”
Section: Ndx Weakly Complements Lethality Due To Complex I Knockdownmentioning
confidence: 96%
See 1 more Smart Citation
“…Yeast Ndi1 expression was shown previously to complement the lethality (at 25°C) of knockdown of subunits of cI [9] in Drosophila, whilst leaving a residual phenotype [32]. We therefore tested whether NDX was able to act similarly.…”
Section: Ndx Weakly Complements Lethality Due To Complex I Knockdownmentioning
confidence: 96%
“…Third, most likely as a consequence of constitutive activity, yeast Ndi1 expression can also be deleterious, under conditions where the ATP supply is limiting. This was found to be the case in two Drosophila models of mitochondrial disease, created by the knockdown of complex IV subunits [26] or the tko 25t mutation affecting mitochondrial protein synthesis [32]. Finally, whereas animals such as C. intestinalis have a single NADH dehydrogenase, yeast has three and plants typically several more.…”
Section: Introductionmentioning
confidence: 93%
“…Our findings are supported by another study which show that mitochondrial mutants have been shown to compensate for their energetic losses (Celotto et al 2011). In addition, Kemppainen et al (2014) found that tko is not rescued by an alternative oxidase, which should alleviate cytochrome oxidase insufficiency. This suggests that tko is a complex mutant with multiple metabolic effects.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case of the tko 25t mutant of D. melanogaster , which harbors a defective mitoribosomal protein S12, leading to deficiency of OXPHOS subunits encoded by the mtDNA, manifesting as developmental delay and several neurological defects that may resemble seizures and hearing loss in human patients. Unexpectedly, the expression of either AOX or Ndi1 in tko 25t mutant flies was unable to rescue these harmful phenotypes (Kemppainen et al, ). Even more unexpected was the fact that bypassing complex I, which has 7 of the 13 proteins encoded by mtDNA, using Ndi1, caused a 50% decrease in the mutant viability, and when AOX was co‐expressed with Ndi1, the phenotype was 100% lethality.…”
Section: Not All Roses: the Tko25t Casementioning
confidence: 99%